Interleukin‐1 blockade in heart failure with preserved ejection fraction: rationale and design of the Diastolic Heart Failure Anakinra Response Trial 2 (D‐HART2). Issue 9 (5th May 2017) - Van Tassell, Benjamin W.; Buckley, Leo F.; Carbone, Salvatore; Trankle, Cory R.; Canada, Justin M.; Dixon, Dave L.; Abouzaki, Nayef; Oddi‐Erdle, Claudia; Biondi‐Zoccai, Giuseppe; Arena, Ross; Abbate, Antonio
Abstract : Heart failure with preserved ejection fraction (HFpEF) now accounts for the majority of confirmed HF cases in the United States. However, there are no highly effective evidence‐based treatments currently available for these patients. Inflammation correlates positively with adverse outcomes in HF patients. Interleukin (IL)‐1, a prototypical inflammatory cytokine, has been implicated as a driver of diastolic dysfunction in preclinical animal models and a pilot clinical trial. The Diastolic Heart Failure Anakinra Response Trial 2 (D‐HART2) is a phase 2, 2:1 randomized, double‐blind, placebo‐controlled clinical trial that will test the hypothesis that IL‐1 blockade with anakinra (recombinant human IL‐1 receptor antagonist) improves (1) cardiorespiratory fitness, (2) objective evidence of diastolic dysfunction, and (3) elevated inflammation in patients with HFpEF (http://www.ClinicalTrials.gov NCT02173548). The co–primary endpoints will be placebo‐corrected interval changes in peak oxygen consumption and ventilatory efficiency at week 12. In addition, secondary and exploratory analyses will investigate the effects of IL‐1 blockade on cardiac structure and function, systemic inflammation, endothelial function, quality of life, body composition, nutritional status, and clinical outcomes. The D‐HART2 clinical trial will add to the growing body of evidence on the role of inflammation in cardiovascular disease, specifically focusing on patients with HFpEF.